Prototype Pengukuran Capaian Pembelajaran Lulusan (CPL) di Universitas Jambi - Wicaksana, Ervan Johan; Said, Yulia Morsa; Dewi, Fatria; Hidayati, Hidayati; Al Arif, Tubagus Zam Zam; Nugraha, Anggit Prima (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The aim of this research is to design a measurement model for Graduate Learning Achievement (GLA) at Jambi University. Internal small group discussions and literature reviews were the choice of data collection models for this development research. The research results reveal that Measuring Graduate Learning Achievements (GLA) is a crucial aspect in ensuring the quality of graduates from a tertiary institution. Quality graduates can increase the competitiveness of human resources both at national and international levels.